A NORMA LINGUÍSTICA E AS GRAMÁTICAS DA RAE: UM ESTUDO CONTRASTIVO: THE LINGUISTIC STANDARD AND GRAMMARS OF THE SAR: A CONTRASTIVE STUDY - Araujo, Leandro Silveira de; Freitas, Fernanda Silva (WEB REVISTA SOCIODIALETO, 2020)
Neste artigo, buscamos descrever as concepções de língua e norma linguística que são veiculadas em gramáticas produzidas pela Real Academia de Española (RAE) – instituição fundada na Espanha, no início do século XVIII, cuja missão principal é a “defesa da unidade da língua”. Foram feitas análises de excertos de dois manuais da instituição, a saber: Esbozo de una nueva gramática de la lengua española (1982) e Nueva gramática de la lengua española - Manual (2010). Na análise, buscamos identificar de qual concepção de Norma Linguística o discurso normativo da RAE mais se aproxima, observando tanto os capítulos introdutórios quanto um capítulo com descrições propriamente ditas. Apresentaremos, aqui, os resultados obtidos ao longo do projeto, que mostraram uma aproximação maior à visão mais prescritiva do termo norma, apesar de todo o projeto de pan-hispanismo que teve como evento importante a publicação dessas duas obras. ABSTRACT: In this paper, we describe how concepts such as ‘language’ and ‘linguistic norm’ are presented on the grammars produced by Real Academia Española (RAE) – an institution founded in Spain in the 18th century who claims to have the mission of “defending the unity of the language”. We made an analysis of two books published by RAE: Esbozo de una nueva gramática de la lengua española (1982) and Nueva gramática de la lengua española - Manual (2010). In the analysis, we seek to identify from which conception of Linguistic Norm the normative discourse of RAE comes closest and we have done that by studying the introductory chapters and a chapter with grammatical content from both publications. Here, we present the results of this research, which showed that the content of both of RAE’s books has more closeness to a more prescriptivist vision of said concepts, even though they are a direct result of the whole pan-hispanic politics promoted by the academy. KEYWORDS: Linguistic norm; Grammaticography; Real Academia Española; Spanish.